Solid-state fermentation of palm kernel cake and composting of oil palm empty-fruit bunches using microbes - Lau, Sharon Yu Ling (2009)
The main concern of the oil palm industry is the growing amount of by-product and wastes produced from the processing of oil palm each year. On average, for every ton of Fresh Fruit Bunches (FFB) processed, 200kg of Empty-Fruit Bunches (EFB), 670kg of Palm Oil Mill Effluent (POME) and 30 kg of Palm Kernel Cake (PKC) are produced. Thus, zero waste strategy has to be adopted to maintain the competitive edge of the booming industry. The experimental work of this study aims to effectively utilize wastes by adopting solid-state fermentation of PKC to convert it to poultry feed and composting of EFB into biofertilizer. PKC is an excellent source of protein and energy and is used extensively in the animal feed industry. However, the main problems faced in the application of PKC as animal feed especially in the non-ruminants are the high fiber content and limitation in amino acid contents of untreated PKC. Thus, solid-state fermentation (SSF) has become a method of preference for the purpose of upgrading the quality of PKC involving the use of microbes as it stimulates the natural environment of most microorganisms. Two species of fungi, Emericella nidulans var. nidulans (Eidam) Vuillermin, Cladosporium herbarum (Pers.) Link BGB and three strains of bacteria Bacillus subtilis , which are good beta-mannanase producing strains were used in combinations to improve the nutritive value of PKC as animal feed through lab-scale solid-state fermentation. With the fermentation operating conditions set to 20% of inoculum, 110% moisture content, pH 7.0 and PKC particle size 0.8 mm, five types of mixed culture treatments were tested. Treatment of PKC with the combination of Emericella nidulans (4DP5) and Bacillus subtilis (7DY7) showed advantages over other treatments. This treatment produced the highest increase in reducing sugar content in PKC to 418.3%. In addition to that, this treatment also gave the lowest increase in aflatoxin level of only 26.8% from 9.99 ppb (aflatoxin content in untreated PKC) to 12.67 ppb, which is below 20 ppb, an acceptable level in animal feed. Simultaneously, EFB and POME have been used extensively as mulch and organic fertilizer in the oil palm plantations. Thus, composting has been singled out as a useful method in converting EFB, which is essentially organic in nature, into humus that is suitable for crop production. One hundred and thirteen potential isolates from the four main groups of microbes namely bacteria, actinomycetes, yeasts and fungi were selected to form a concoction of inoculum, which was applied during composting of EFB in a model backyard-scale system. Mechanically-shredded EFB and raw POME, subjected to an open system composting employing the 4 days turn-over method help to accelerate the rate of EFB composting. The rate of EFB composting was sped up to within 28 days. With the aide of inocula, EFB composting was further improved in terms of maturity and nitrogen and phosphorus content in the compost. EFB added with compost, nitrogen-fixing and phosphate-solubilizing inoculum (Pile A) yielded the carbon/nitrogen value of 18.7 on day 28 from the initial value of 71 compared to 21.2 (Pile B) and 26.4 (control). Pile A also showed an increase of 2.19% in nitrogen content and 0.18% in phosphorus content.